PENGUKURAN PENGUNGKAPAN SUSTAINABILITY REPORTING HIMPUNAN BANK NEGARA (HIMBARA) - Ahmad; Azmi Kurnia Izzati; Agus Munandar (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
The Sustainability Report is seen as a form of communication between companies and stakeholders to provide an overview of various social performances so that stakeholders can measure, compare and evaluate them. In its preparation, one of the guidelines used is called the GRI Standards which is also a benchmark for the amount of disclosure that should be presented in the SR. The object of this research is the SR for 2018-2020 belonging to the banks that are members of the Himbara, namely Bank Mandiri, BNI, BRI and BTN which are analyzed using content analysis. The results of the study show that these banks are strong in general disclosure such as of organizational profile, strategy, ethics and integrity, stakeholder engagement and reporting practices but still require considerable improvement in the categories of governance, economics, environment and social.